Estimating the specific yield of the Pampeano aquifer, Argentina, using superconducting gravimeter data - Pendiuk, Jonatan Emmanuel (2020)
Specific yield is a key parameter for the sustainable management of unconfined aquifers, since it relates water-table fluctuations to aquifer storage-changes and thus impacts water supply. However, estimating specific yield is still a challenge due to theoretical and methodological limitations. Water-storage changes in the aquifer and in the overlying unsaturated soil profile cause local changes in gravity that can be recorded by high-precision superconducting gravimeters. In this work, a novel methodology to estimate specific yield from superconducting gravimeter data is presented. The proposed methodology is based on a hydrogravimetric model that estimates the gravity response due to the loss and gain of water mass in the soil profile using rainfall, water-table and air-temperature data. The model is applied to a study site of the Pampeano aquifer in Argentina where a continuous 1-year record of superconducting gravimeter measurements is available. The specific yield value obtained using this methodology is 0.11 ± 0.039, which is validated by means of a long-term pumping test performed at the study site. The proposed method constitutes a promising alternative to the available tools for estimating specific yield, by taking advantage of superconducting gravity data.